Hydroxychalcones as Herbicides - Garrido, Raphael Mota [UNESP]; Dayan, Franck Emmanuel; Ozanique, Patrick Rômbola [UNESP]; Regasini, Luis Octavio [UNESP]; Kolb, Rosana Marta [UNESP] (MDPI, 2025)
Efforts to develop weed management alternatives are urgently required due to various challenges, such as declining crop yields, rising production costs, and the growing prevalence of herbicide-resistant weed species. Chalcones occur in nature and have phytotoxic potential and concise synthesis; additionally, they are multifunctional, with diverse biomolecular targets and a broad spectrum of biological activities. This study sought to assess the herbicidal potential of 3′-hydroxychalcones against weed species under laboratory conditions. Their effects were investigated using germination bioassays, early growth measurements, and the seedling vigor index, all prepared with a concentration of 1 × 10−3 mol L−1 3′-hydroxychalcones. 3′-Hydroxy-4-pyridyl-chalcone caused the greatest inhibition (81%) of the seedling length in Urochloa decumbens. Other 3′-hydroxychalcones also caused large initial growth reductions, such as 3′-hydroxy-4-pyridyl-chalcone (75%) and 3′-hydroxy-4-nitrochalcone (68%) in Digitaria insularis and 3′-hydroxy-4-bromochalcone (73%) in Raphanus raphanistrum. The greatest reduction in the seedling vigor index was 81% in D. insularis treated with the 3′-hydroxy-4-bromochalcone. The same 3′-hydroxychalcone caused an 80% reduction in Amaranthus viridis. In conclusion, 3′-hydroxychalcones exhibit herbicidal activity, suggesting they could serve as a solution for future weed management strategies.
Keywords: herbicidal activity; hydroxylated chalcones; phytotoxicity